Experimental exposure to trace metals affects plumage bacterial community in the feral pigeon. (1st February 2016) - Chatelain, M.; Frantz, A.; Gasparini, J.; Leclaire, S.
Abstract : Bacteria are fundamental associates of animals, and recent studies have highlighted their major role in host behaviour, immunity or reproductive investment. Thus, any environmental factor modifying bacterial community may affect host fitness. In birds, trace metals emitted by anthropogenic activities accumulate onto the plumage where they may alter bacterial community and ultimately affect bird fitness. Although trace metals are current major environmental issues in urban habitats, their effects on feather bacterial community have never been investigated. Here, we supplemented feral pigeons Columba livia, an emblematic urban species, with zinc and/or lead in drinking and bath water. As expected, lead and zinc supplementations modified plumage bacterial community composition. Zinc decreased bacterial load, while lead decreased bacterial richness and the frequency of preening behaviour in birds, known to regulate feather bacteria. Our results demonstrate for the first time the effects of common urban trace metals on plumage bacterial community and shed light on one of the mechanisms by which trace metals can affect bird fitness. Further studies are now needed to investigate how this effect modulates avian life history traits known to depend on plumage bacterial community.